Validation of a conceptual framework aimed to standardize and compare care integration initiatives: the project INTEGRATE framework. Issue 1 (2nd January 2022) - Calciolari, S; González Ortiz, L; Goodwin, N; Stein, V
ABSTRACT: The development of integrated care initiatives to overcome service delivery fragmentation has become a global concern. Yet, the lack of guidance in their design and delivery has led to a high risk of project failure. Several authors have proposed driving ideas and strategies to foster care integration but a comprehensive conceptual framework building on the evidence and different perspectives of scientific contributions is still needed. The objective of this article is to explain the process of development and validation of a comprehensive framework that could be used either to standardize descriptions of existing care integration initiatives or as a conceptual basis for reflecting on the effective design of new programs or projects. In an initial phase, we used a comprehensive list of 175 items resulting from a literature review in order to identify a 'core set' of relevant framework items. subsequent phases, we validated the newly developed framework. External experts supported the validation phases. The iteration process resulted in a framework of 40 items grouped into seven dimensions: Person-centered care, Clinical integration, Professional integration, Organizational integration, Systemic integration, Functional integration, and Normative integration. The validated framework proved to be understandable and relevant to identify analytical aspects fostering care integration. It could be adapted as a useful tool to inform the design and implementation of new integrated care interventions as well as to generate standardized description of initiatives to perform insightful comparisons.